Evidence-based practice in nursing informatics : concepts and applications - Cashin, Andrew, 1966-; Cook, Robyn, 1959- (Hershey, PA : Medical Information Science Reference, 2011)
'This book provides relevant theoretical frameworks and empirical research findings in the area of nursing informatics, critiquing fundamental concepts such as evidence based practice and examining possible applications of such concepts in the contemporary context of nursing informatics'--Provided by publisher.
Includes bibliographical references (p. 253-287) and index.
Keywords: Nursing informatics; Evidence-Based Nursing